THE PRAGMATIC AND GRAMMATICAL FUNCTIONS OF DMS IN AMERICAN AND GEORGIAN COMMENCEMENT SPEECHES - Buskivadze, Khatia (Online Journal of Humanities ETAGTSU, 2021)
This paper investigates the use of discourse markers in two commencement speeches given by American and Georgian speakers from the perspective of Pragmatics. The study is specifically based on Fraser’s taxonomy of discourse markers according to their pragmatic and metalinguistic functions. This theoretical framework is concerned with language in use, giving more importance to the context than to the text of utterances. The authors attempt: (1)to look at which DMs (Discourse Markers) are used in particular discourse; (2) to provide a through explanation of addresser’s communicative intentions based on their choice of DMs; (3) to identify mainly functional (and linguistic) characteristics of English DMs in comparison to their selected Georgian equivalents. Findings of qualitative and quantitative analysis reveal some similarities and differences regarding the ratio of using each type of DMs. Full Text (PDF)